2024
DOI: 10.1038/s41593-024-01638-y
|View full text |Cite|
|
Sign up to set email alerts
|

Brain clearance is reduced during sleep and anesthesia

Andawei Miao,
Tianyuan Luo,
Bryan Hsieh
et al.

Abstract: It has been suggested that the function of sleep is to actively clear metabolites and toxins from the brain. Enhanced clearance is also said to occur during anesthesia. Here, we measure clearance and movement of fluorescent molecules in the brains of male mice and show that movement is, in fact, independent of sleep and wake or anesthesia. Moreover, we show that brain clearance is markedly reduced, not increased, during sleep and anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Chronic sleep disturbances can impair the efficiency of the glymphatic system, leading to a buildup of beta-amyloid, which can further disrupt sleep, creating a vicious cycle [10]. Although recent evidence has challenged the role of sleep in clearing the extracellular space from potentially accumulating toxins [40], the evidence supporting sleep in preventing beta-amyloid accumulation remains robust [2]. Consistent with these findings, we observed that sleep enhancement via rocking reduced beta-amyloid levels in the brain.…”
Section: Discussionsupporting
confidence: 83%
“…Chronic sleep disturbances can impair the efficiency of the glymphatic system, leading to a buildup of beta-amyloid, which can further disrupt sleep, creating a vicious cycle [10]. Although recent evidence has challenged the role of sleep in clearing the extracellular space from potentially accumulating toxins [40], the evidence supporting sleep in preventing beta-amyloid accumulation remains robust [2]. Consistent with these findings, we observed that sleep enhancement via rocking reduced beta-amyloid levels in the brain.…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, risk factors that should also be taken into consideration in the binomial sleep-glymphatic system include the impact of elevated ambient temperatures, affecting not only sleep but also thermoregulation and autonomic system reactivity [20]. The convergence of evidence from animal models also demonstrated that brain clearance is reduced during sleep and in the presence of anesthetics, especially dexmedetomidine, ketamine-xylazine and pentobarbital [21]. Why this occurs remains a matter of discussion.…”
Section: The Second Question: Factors Influencing/modulating the Glym...mentioning
confidence: 99%